MENINGKATKAN MOTIVASI BELAJAR ANAK KELOMPOK A TK MASILOM TIBOBO MELALUI METODE BERMAIN PERAN - Rosita Wondal; Karil Afrida (Jurnal Ilmiah Cahaya Paud, 2015)
Motivation is processes that encourages, direct and maintain human behavior towards the achievement of objectives. The method is a way of role play of mastery learning materials through the development of imagination and appreciation of students. This type of research is classroom action which subject of research were students in group A TK Masilom Tibobo, the number of 16 children, the study conducted by two cycles. The results obtained through the role play activities can increase children’s ability to motivate a group of kindergarten Masilom Tibobo, with a big increase in the thoroughness of the child’s motivation to learn cycle I to cycle II which is 12,5 %. Key words: motivation, study, methods, role-play